Dinamika Konflik Etnis di Toboali Kabupaten Bangka Selatan - Sefri Barkah; - - Mulyanto; Kgs. Muhamammad Sobri (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
This research aims to observe about the main source of ethnic conflict in Toboali South Bangka, any parts that involved in this ethnic conflict, what stages of the dynamics of ethnic conflict and conflict resolution models such as what needs to be implemented in an attempt to create a peace between these two ethnic groups. This research is a qualitative research using the paradigm of constructivism and the intrinsic case study research strategy. In determining the informant is done by using purposive sampling method. Data was collected by in-depth interviews, participant observation and documentation of the number of informants as many as seventeen.Results from this study indicate that the source of ethnic conflict in Toboali there are three sources: 1). Scramble of Timah Resources. 2) Regarding the difference in interest Manage Access Sea. 3). The existence of social segregation. The period of conflict dynamics can be identified into 4 periods they are 1) The beginning of migration of Selapan migrant to Toboali untill appear of bad prejudice (Praconflict Periode 1980-2001). 2). Beginning of digging of Tin by people, untill appear of confrontation actions (Confrontation Periode 2001-2011). 3) Agression action by group of Bangka Ethnic to residential of Selapan Ethnic, untill demonstration action that ended by commotion (Crisis Period 2011-2014). 4). Publication of Inpres No.1 on 2014 about handling safety disturbances intra country by central government (Pasca Conflict Periode 2014-now). Then the actors that involved in the conflict can be identified from group of Bangka ethnic including a). The Leader of Bangka Fisherman Association. b). The Social Figure of Bangka Ethnic c). The Racketeer of mining industriesÂ Â While an actor from Selapan ethnic was Tin owner that was a Selapan social figure. Recommendations of conflict resolution that offered is mediation to accommodate all interests and empowering groups involved.